Resistin exerts a beneficial role in atherosclerotic plaque inflammation by inhibiting neutrophil migration. (1st December 2018) - Liberale, Luca; Bertolotto, Maria; Carbone, Federico; Contini, Paola; Wüst, Patricia; Spinella, Giovanni; Pane, Bianca; Palombo, Domenico; Bonaventura, Aldo; Pende, Aldo; Mach, François; Dallegri, Franco; et al.
Abstract: Background: Neutrophil functions have been shown to be modulated by adipocytokines during atherogenesis. The immuno-regulatory role of resistin on neutrophil-mediated activities in atherosclerotic patients remains elusive. Here, we aimed at exploring the association between serum levels of resistin and neutrophil products either in the systemic circulation or within plaques in a cohort of patients with severe carotid plaque stenosis undergoing endarterectomy. In addition, we assessed the effects of resistin on neutrophil pro-atherosclerotic functions in vitro. Methods: Inflammatory biomarkers, neutrophil products and resistin levels were assessed in patients' sera and carotid plaques by ELISA and immunohistochemistry analysis. In vitro, human primary neutrophils isolated from healthy donors were assessed on different substrate cultures for: degranulation (by ELISA), migration (by microchemotaxis Boyden chamber), F-actin polymerization (by fluorescent assay), integrin and chemokine receptor expression (by flow cytometry) and apoptosis (by both morphologic analysis and flow cytometry). Results: Serum resistin was positively correlated with serum levels of neutrophil granule products, but inversely with intraplaque neutrophil and MMP-9 contents. In vitro, resistin was detected in supernatants of degranulating neutrophils and positively correlated with other granule products. Although resistin did not affect neutrophil degranulation, apoptosis and integrin or chemokine receptor expression, pre-incubation with human recombinant resistin abrogated CXCL8-induced neutrophil migration and F-actin polymerization by inhibiting ERK2 phosphorylation. Conclusion: Resistin can be released by degranulating neutrophils and blunts neutrophil plaque infiltration by modulating their migration towards known atherosclerotic mediators. These results suggest a potential immunoregulatory role of resistin in inhibiting neutrophil-mediated atherosclerotic activities. Highlights: Resistin is positively correlated with neutrophil granule products in serum. Resistin is inversely correlated with intraplaque neutrophil and MMP-9 contents. Resistin does not affect neutrophil degranulation and apoptosis. Resistin abrogates CXCL8-induced neutrophil migration in vitro.